The Household Water Insecurity Experiences (HWISE) Scale: comparison scores from 27 sites in 22 countries - Justin Stoler (IWA Publishing, 2021)
Household survey data from 27 sites in 22 countries were collected in 2017–2018 in order to construct and validate a cross-cultural household-level water insecurity scale. The resultant Household Water Insecurity Experiences (HWISE) scale presents a useful tool for monitoring and evaluating water interventions as a complement to traditional metrics used by the development community. It can also help track progress toward achievement of Sustainable Development Goal 6 ‘clean water and sanitation for all’. We present HWISE scale scores from 27 sites as comparative data for future studies using the HWISE scale in low- and middle-income contexts. Site-level mean scores for HWISE-12 (scored 0–36) ranged from 1.64 (SD 4.22) in Pune, India, to 20.90 (7.50) in Cartagena, Colombia, while site-level mean scores for HWISE-4 (scored 0–12) ranged from 0.51 (1.50) in Pune, India, to 8.21 (2.55) in Punjab, Pakistan. Scores tended to be higher in the dry season as expected. Data from this first implementation of the HWISE scale demonstrate the diversity of water insecurity within and across communities and can help to situate findings from future applications of this tool. HIGHLIGHTS We present comparison scores of the Household Water Insecurity Experiences (HWISE) scale, a novel household water insecurity index validated for use in low- and middle-income countries.; These scores can aid interpretation of future implementation of the HWISE scale.; The HWISE scale should still be evaluated in new contexts, such as high-income settings.;